Produksi Abon Ikan Lele Sebagai Inovasi Pengelolahan Ikan Lele Dan Usaha Untuk Meningkatkan Perekonomian Masyarakat Desa Tanjung Batu Itam - Guspiarsi, Yulis; Robiansyah, Robiansyah; Febiana, Tania (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
This article discusses the implementation of the IAIN SAS BABEL Real Work Lecture (KKN) program in Tanjung Batu Itam Village as a form of community service. Tanjung Batu Itam Village is one of the villages in Simpang Pesak District, East Belitung Regency. Tanjung Batu Itam Village has various potentials, one potential that stands out and can be exploited easily in Tanjung Batu Itam Village is cultivating freshwater fish such as catfish. Catfish cultivation in Tanjung Batu Itam Village is managed by a youth group called POKDAKAN (Fish Cultivator Group) Muda Jaya Millenial. In order to increase the economic value of a product, catfish can be made into a processed product so that it has a higher selling price compared to raw fish. Shredded meat is a long-lasting food that has high protein and low cholesterol levels. Catfish meat can be used as raw material for making shredded meat. The aim of making freshwater fish floss is to develop the existing potential of Tanjung Batu Itam Village, produce processed food products, and open new business areas in order to improve the economy of the people of Tanjung Batu Itam Village.